The Influence of Organizational Culture and Work Environment on Employee Performance Mediated by Leadership at the Jakarta Mass Rapid Transit (MRT Jakarta) Station - Salam, Mochamad Darda Darus; Zaharuddin, Zaharuddin; Sembada, Gada (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study is motivated by the organizational demands in the era of globalization and technological disruption to maintain competitiveness through the optimization of human resource performance. The objective is to analyze the influence of organizational culture and work environment on employee performance at PT MRT Jakarta, as well as to evaluate the mediating role of leadership in this relationship. A quantitative approach was employed using a survey method involving 265 respondents selected through accidental sampling from a population of 783 operational station employees. Data were collected using a closed-ended questionnaire based on a five-point Likert scale and analyzed through multiple linear regression, t-test, F-test, and Sobel test. The results indicate that organizational culture and work environment significantly influence employee performance, both directly and indirectly through leadership as a mediating variable. A disciplined, service-oriented organizational culture, a safe and comfortable work environment, and transformational leadership have been proven to enhance performance quality. These findings underscore the importance of synergy between structural and cultural aspects in human resource management policies. The recommended policy implications include strengthening organizational cultural values, improving work environments focused on health and ergonomics, and developing sustainable leadership training programs to support the achievement of strategic organizational goals.